JURIDICAL REVIEW HATE SPEECH Law No. 11 YEAR 2008 JUNCTO Law No. 19 OF 2016 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS IN PROVIDING COMMUNICATION ETHICS EDUCATION IN SOCIAL MEDIA - Ida Ayu Putu Anggie , Sinthiya (Progressive Law Review, 2019)
Social media is an online media, which makes it easy for us to communicate openly; social media is able to shift conventional mass media in spreading the news. Through social media everyone gets an expression space that is free and easy to communicate, free to express, criticize and share on social media. But in its journey social media provides a space of freedom that transcends boundaries and strikes norms and ethics. Now the easier it is for someone to do hate speech in the form of provocation, incitement, or insult to other individuals or groups in terms of various aspects such as race, color, ethnicity, gender, disability to sexual orientation, citizenship and religion on social media. The legal rules regarding hate speech are regulated in Article 310 and 311 of the Criminal Code and Law Number 40 of 2008 Law Number 11 of 2008. Building good ethics on social media is the rule of law that social media users can know and understand the limitations in communicating on social media so as to create good, polite, responsible and civilized communication ethics